EXPLAINING FRAUDULENT FINANCIAL REPORTING THROUGH THE FRAUD HEXAGON IN INDONESIAN STATE-OWNED ENTERPRISES - Dian Juweni Putri; Rita Anugerah; M Rasuli (Universitas Riau, 2026)
This study aims to analyze the influence of the in the Fraud Hexagon theory on fraudulent financial reporting in BUMN listed on the Indonesia Stock Exchange. The fraud hexagon is an extension of previous theories (Fraud Triangle, Diamond, and Pentagon) by adding collusion as a new factor, resulting in six key elements: stimulus (financial target, financial stability, external pressure), capability (CEO education), opportunity (ineffective monitoring, nature of industry), rationalization (total accrual ratio), ego (frequent number of CEO’s picture), and collusion (market performance). This research uses a quantitative approach with logistic regression analysis, utilizing SPSS version 26.0 software. The sample used in this study consisted of 75 samples of BUMN listed on the Indonesia Stock Exchange during 2020-2024. The sample in this study was taken using a purposive sampling method. Fraudulent financial reporting is measured using the F-score model. The results show that financial target, financial stability, external pressure, ineffective monitoring, nature of industry, total accrual ratio, and market performance have a significant effect on fraudulent financial reporting. Meanwhile, CEO education and the frequent number of CEO’s picture do not show a significant effect on fraudulent financial reporting.